(untitled) (Bangladesh Journal of Agricultural Research, 2023)
This article empirically investigates poverty, food security and nutritional status of selected former enclave households. Binary logistic regression was carried out to find out the factors affecting food security of the households. Following simple random sampling technique, a sample of 80 households from two villages of Dibiganj upazila of Panchagarh district of Bangladesh was surveyed in January 2020. On an average, they consumed 20 food items of which their daily per capita intake was 1414.52 gm. Mean of daily per capita protein and calorie intake was 63.14 gm. and 1619.67 Kcal, respectively. Rice occupied the major contributing source of protein and calorie intake as per capita consumption of rice was highest among all other food items (609.35 gm.). Among the respondents, 61.25% belonged to ultra-poor following by hard core poor (20%) and absolute poor (7.5%). Based on FCS, 81.25% of them were in poor diet clusters but consequently 91.25% of them belonged to high dietary diversity as indicated by household dietary diversity score. Assessment of CSI and HFIAS indicated that most of the sample households were suffering from moderately to severely food insecure. But based on MAHFP, 20% of the respondents were found to be food insecure as they had food provisioning for 0- 9 months out of 12 months. At the same time, 51.25% of the sample households were underweight based on their BMI. There was no household member whose physical feature was found to be obese based on BMI characterization. The result of the binary logistic regression shows that food security is positively correlated with total land size and family consumption of food. So, diversification of crop production and diversification of family consumption can be the recommended steps for the enclaves’ households to upgrade their food and nutrition security status Bangladesh J. Agril. Res. 46(4): 353-372, December 2021